Some Variables Affecting the Formulation of Pentoxifylline (PTX) as a Solid Sustained Release Dosage Form - H. Hussain, Ahmed; I.Khalil, Yehia (Iraqi Journal of Pharmaceutical Sciences, 2017)
An inert matrix that is used to control the release of (PTX) was prepared using Eudragit RL100 and RSPM types as matrix forming agent . The matrices were prepared by either dry granulation(slugging) , or wet granulation method using chloroform as a solvent evaporation vehichle. The cumulative release was adjusted by using polyvinylpyrollidone (PVP) or ethylcellulose (EC) polymers .The results indicated that both methods of preparation were valid for incorporation PTX as a sustained release granules .Moreover ,the results revealed that best polymer used was Eudragit RSPM in 3:20 polymer drug ratio .Besides to that , the results indicated that the release profiles were affected by pH- medium , PVP and EC addition as an enhancer or retardant polymer used respectively. As well as to the method of preparation . Key words : Pentoxifylline Sustained Retease , Eudragit RS , RL .